Evaluation of a tryptase depletion index for better pathologic identification of mast cell activation syndrome - Zienkiewicz, Tomasz; Homann, Jürgen; Mücke, Martin; Seidel, Holger; Hertfelder, Hans-Jörg; Weinstock, Leonard B.; Afrin, Lawrence B.; Molderings, Gerhard J. (Zeitschrift für Gastroenterologie, 2022)
Background Laboratory evidence supporting diagnosis of the prevalent condition of mast cell activation syndrome (MCAS) currently includes elevated levels in blood or urine of mediators relatively specific to mast cells (MCs) and/or increased numbers of MCs in luminal gastrointestinal (GI) tract tissues. However, identification of elevated mediators is technically challenging and expensive, and controversy persists regarding the normal ranges of numbers/counts of MCs in various GI tract segments, let alone challenges in determining how many of the visualized MCs are activated. To aid diagnosis of MCAS, we developed a potential new approach for the pathologist to identify the extent of GI tract MC activation easily and inexpensively.Participants and Methods Visualization of MCs in gastrointestinal biopsies from 251 patients vs. 95 controls using antibodies against CD117 and tryptase; MC counting per mm2; calculation of the difference between the CD117-positive MCs (identifying all MCs) vs. tryptase-positive MCs (identifying non-activated tryptase-containing MCs), which we define as the tryptase depletion index (TDI).Results Mean total MC counts did not differ significantly between patients and controls, but mean TDIs differed significantly. Non-overlapping confidence intervals at the 99.9% level identified cut-offs of TDIs between patients vs. controls of 26, 45 and 32 MCs/mm2 in gastric antrum, duodenum, and colon, respectively.Conclusions The TDI may discriminate between MCAS patients vs. controls. If this preliminary work can be independently confirmed, the TDI may become a useful additional minor diagnostic criterion for MCAS.
Keywords: Mastzellaktivierungssyndrom; Mastzelldichte; Mastzellaktivität; diagnostische Kriterien; CD117-Antikörperfärbung; Tryptase-Antikörperfärbung; Tryptasefreisetzungsindex